2022
DOI: 10.3389/fcimb.2022.967584
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the metagenomic next-generation sequencing performance in pathogenic detection in patients with spinal infection

Abstract: Spinal infection is a rarely occurred pathology, whose diagnosis remains a major challenge due to the low sensitivity of culturing techniques. Metagenomic next-generation sequencing (mNGS) is a novel approach to identify the pathogenic organisms in infectious diseases. In this study, mNGS technology was adopted for pathogenic detection in spinal infection from the tissue and pus samples. Additionally, the diagnostic performance of mNGS for spinal infection was evaluated, by comparing it with that of the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…This suggests that sampling method and site may have a potential impact on mNGS outcomes, a topic not yet thoroughly investigated in the literature. This study attempted to explore the impact of pus and tissue sample types on the positive rate of mNGS, but the ndings were not statistically signi cant, aligning with previous research [31].Additionally, the high sensitivity of mNGS may also lead to a higher false-positive rate, which might contribute to the lower speci city of mNGS compared to traditional microbial cultures observed in this study. Finally, there is a time lapse from sample collection to result analysis, rendering mNGS potentially unsuitable in certain urgent scenarios.…”
Section: Discussionsupporting
confidence: 47%
“…This suggests that sampling method and site may have a potential impact on mNGS outcomes, a topic not yet thoroughly investigated in the literature. This study attempted to explore the impact of pus and tissue sample types on the positive rate of mNGS, but the ndings were not statistically signi cant, aligning with previous research [31].Additionally, the high sensitivity of mNGS may also lead to a higher false-positive rate, which might contribute to the lower speci city of mNGS compared to traditional microbial cultures observed in this study. Finally, there is a time lapse from sample collection to result analysis, rendering mNGS potentially unsuitable in certain urgent scenarios.…”
Section: Discussionsupporting
confidence: 47%
“…28 mNGS is increasingly used for diagnosing atypical and rare infectious diseases and has shown significantly higher sensitivity than traditional microbial culture for identifying pathogens in spinal infections, thereby improving pathogen detection rates. 29,30 In the present case, the imaging findings showed infectious lesions of the thoracic spine including destruction of the 5-6 vertebral bodies, intervertebral space stenosis, and a soft-tissue mass surrounding the affected area. Traditional microbial cultures were negative.…”
Section: Discussionmentioning
confidence: 47%
“…Numerous recent studies have demonstrated that metagenomic sequencing plays a pivotal role in successful pathogen recognition for infections characterized by atypical clinical symptoms that are unidentifiable through traditional etiological detection methods or caused by unknown pathogens [ 66 , 67 ]. These findings underscore the pivotal role of metagenomic sequencing in guiding drug administration and enhancing clinical outcomes for patients with spinal infection, particularly when conventional methods fail to identify the pathogen [ 68 ]. In this study, the pathological examination revealed the presence of fungal mycelium in serial sections of the vertebral lesion tissue, as indicated by positive results of PASM and PAS staining.…”
Section: Discussionmentioning
confidence: 99%